THE COIN HOARD FROM THE SARNITSA VILLAGE, HASKOVO REGION. TOWARDS THE QUESTION OF CLARIFYING THE ORIGIN OF THASOS IMITATIONS OR BARBARIZATION - Prokopov, I.; Slavova, M. (Материалы по археологии и истории античного и средневекового Причерноморья)
The article examines one of the well-preserved coin hoards consisting exclusively of imitations or barbarizations of tetradrachms traditionally minted on the island of Thasos. A homogeneous coin find of this kind is characteristic of the area where the latest coinage took place. Actually, these are the last-ever tetradrachms minted in Thrace in the 1stcentury BCE. Since numismatics still hardly can tell “imitation” from “barbarization” with any certainty, both are still used here on equal terms. However, the long-standing dispute over which coins are real imitations of Thasos tetradrachms is about to be settled. The large series of tetradrachms, which can hardly be differ from the original Thasos ones and are called “of the Thasos type”, should be defined as imitations. They were issued by the Roman administration of the Balkans. All the rest, which lack a clear issuer and generally go far beyond the limits of good style and inscription, can be called barbarized. This is why the coin hoard from Sarnitsa is worth republishing.